PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN DI RESTORAN BEBEK DAN AYAM GORENG PAK NDUT SOLO - Hayati, Yetti Hunsul; Sekartaji, Gracia (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2015)
ABSTRACTThis study is about the Effect of Product Quality, Customer Satisfaction and Influence Effect of productquality to customer satisfaction conducted on Eating Duck and Chicken Fry Pak Ndutâs Restaurant. Theanalytical method used is quantitative statistics. The analysis of the data used is Analysis CorrelationCoefficient. Research results revealed the fact that the product quality affects customer satisfaction, it canbe seen in the table Correlation obtained for rxy 0710, and the value r tabel on 398 df is 0.098. it meansthere is a positive relationship between the products to customer satisfaction at home eating duck andchicken fried Pak Ndut Solo. Based on the index level of customer satisfaction can be seen that theaverage Tki is 100.1%, which means that consumers are satisfied with the quality of existing products athome eating duck and chicken fried Pak Ndut Solo. When viewed by test f and t, f test states that the valueof F count> F table that is 89.621> 1.96 by t-test and stated that t has a value greater than the value ttable is 1.966> 0.05, which means There is a significant relationship between the independent variables,Quality Products from duck and chicken fried Pak NdutâS restaurant with Consumer Satisfaction.Keywords: Product quality and consumer satisfaction